A first-principles prediction of electronic, mechanical and thermodynamic properties of α-LuAlB4 and β-LuAlB4 ceramics. (September 2021) - Bao, Weizong; Xiang, Tao; Cai, Zeyun; Chen, Jie; Bao, Longke; Xie, Guoqiang
Abstract: In this work, the electronic, mechanical and thermodynamic properties of two polymorphs of LuAlB4 ceramics ( α -LuAlB4 and β -LuAlB4 ) were predicted through first-principles calculations. The formation enthalpy of α -LuAlB4 and β -LuAlB4 is −1.433 kJ/mol and −1.429 kJ/mol, respectively, indicating that LuAlB4 ceramics are stable. Crystal structure and electronic structure analysis revealed that strong B–B bonds greatly contributes to the high hardness of LuAlB4 ceramics. The analysis of state density showed that LuAlB4 is a layered ternary boride with metallic properties. Elastic anisotropy indexes, 3D surface constructions and 2D projections of elastic modulus showed that the elastic anisotropy of α -LuAlB4 is higher than β -LuAlB4 . In addition, the phonon dispersion curves verified the thermodynamic stability of LuAlB4 ceramics. Finally, according to elastic constants and modulus, the Debye temperature, directional sound velocities and thermal conductivities of LuAlB4 ceramics were discussed. Highlights: The metal characteristics of LuAlB4 mainly composed of Lu- p, Lu- d, Al- p and B- p state decisions. Judging by Poisson's ratio v and Pugh's modulus ratio G / B, the plasticity of LuAlB4 is better than that of other Lu-B system ceramics that have been reported. The elastic universal anisotropy index A U indicates that the order of elastic anisotropy is: α-LuAlB4 > β-LuAlB4 .